Valence-controlled protein conjugation on nanoparticles via re-arrangeable multivalent interactions of tandem repeat protein chains. Issue 25 (13th June 2022) - Choi, Hyeongjoo; Jung, Yongwon
Abstract : Tandem repeat protein chains were wrapped around nanoparticles via re-arrangeable multivalent interactions for valence controlled protein conjugation. Abstract : Precise control of the number of conjugated proteins on a nanoparticle surface has long been a highly challenging task. Here, we developed a one-pot, purification-free strategy for valency-controlled conjugation of tandem repeat protein chains on gold nanoparticles. Protein chains were designed to contain multiple, regularly spaced binding modules, which can multivalently interact with coating molecules on nanoparticle surfaces. We discovered that a slow increase of this interaction strength facilitates full participation of repeated binding modules on a protein chain for surface binding (as well as dynamic rearrangement) on a single nanoparticle, which resulted in stable protein chain wrapping around nanoparticles. By varying the protein chain length, a defined number of protein chains were conjugated on gold nanoparticles with difference sizes. Various high-order nanoparticle structures were accurately assembled with these valence-controlled protein–particle conjugates. The present strategy offers a highly dynamic but controlled protein coating approach on solid surfaces of diverse nanostructures. In addition, this work also provides a valuable clue to understand dynamic binding processes of multivalent repeat proteins.